Identifying efficient practices in inclusive communication for people with complex communication needs - Calleja-Reina, Marina; Luque, María Luisa; Sotillo, María (Revista de Investigación en Logopedia, 2026)
Research and professional practice related to intervention programs with inclusive communication objectives highlight the need for intervention practices that have been endorsed by criteria for effective outcomes.This paper analyzes the types of intervention practices and highlights the importance of effective practices in inclusive communication, especially for groups of people with complex communication needs. The results of an analytical study conducted using the Delphi method with groups of professionals with expertise in communication and language interventions for people with complex communication needs are presented. The aim is to extract common elements among effective practices that would be useful for designing effective intervention programs for people with complex communication needs. The results of the study are complemented by the incorporation of first-hand experiences from professionals with expertise in communication and language intervention programs for people with complex communication needs.
Keywords: Inclusive Communication; Complex communication needs; efficient practices